PEMBUATAN VIDEO YOUTUBE DAN TIKTOK SEBAGAI SARANA DIGITAL MARKETING PADA PESANTREN YAA BUNAYYA PURWAKARTA - Hesti Rian; Evalina Evalina; Bakri Bakri; Ermanuri Ermanuri; Handa Gustiawan (JURNAL ABDIMAS PLJ, 2022)
Yaa Bunaya Islamic Boarding School located in Purwakarta is a growing Islamic boarding school. The administrators of the Yaa Bunaya Islamic Boarding School want to expand the marketing of the Islamic boarding school which so far has only been done by word of mouth. Currently, Islamic boarding school administrators want to use social media, especially Youtube and Tiktok, as a digital marketing tool that can be used to expand the marketing of Islamic boarding schools with the aim of getting more new students quickly. It is hoped that the training and assistance provided by the team of community service lecturers in making videos for Youtube and TikTok can help increase the income of the number of new students at the Yaa Bunaya Islamic Boarding School in Purwakarta.Keyword: youtube, tiktok, digital marketing